Differential performance in high vs. low stakes tests: evidence from the GRE test - Analia Schlosser; Zvika Neeman; Yigal Attali (Center for Economic Studies and ifo Institute (CESifo), 2019)
We study how different demographic groups respond to incentives by comparing their performance in “high” and “low” stakes situations. The high stakes situation is the GRE examination and the low stakes situation is a voluntary experimental section of the GRE. We find that Males exhibit a larger drop in performance between the high and low stakes examinations than females, and Whites exhibit a larger drop in performance compared to minorities. Differences between high and low stakes tests are partly explained by the fact that males and whites exert lower effort in low stakes tests compared to females and minorities.
Keywords: C93; I23; I24; J15; J16; J24; 330; high stakes; low stakes; GRE; incentives; experiment; performance; gender gap; race gap